A PSYCHOLINGUISTIC ANALYSIS OF MENTAL STRENGTH OF COLLEGE STUDENT TOWARDS LECTURER - Jessinia Laracroft Korengkeng; Mister Gidion Maru; Sarah Kamagi (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The research has the purpose of revealing the mental strength or mentality of college students. This research was done qualitatively which means the data are in the form of words, so there are no diagrams, formulas, or numbers in the data. In executing this research, the researcher used interview technique in revealing the students’ mental strength. The result of the study explained that mental strength is crucial in college life. The condition of the students’ mental strength could greatly impact their well-being, performances in academic and overall success in college life. The factors that affect their mental strength are their courage, toughness patience and endurance in facing the lecturers and their lectures. In the end, it can be concluded that students’ mental strength affects their daily life in the college while the factors affecting their mental are all depending on their ability in enduring the challenges.